Comparison of corrosion rates obtained from laboratory and field data. Issue 6 (27th April 2016) - Ruppert, J.; Frimmel, F.; Baier, R.; Binder, G.
Abstract : Generally, corrosion rates for sheet pile walls observed in nature and those obtained in the laboratory are different. In order to compare natural and laboratory corrosion rates, corrosion tests were carried out with an electrochemical corrosion cell. Various mild steel samples which were taken out from different sheet pile structures were examined with synthetic brackish water and synthetic seawater as immersion media. It was ensured that the electrical conductivity and the pH‐values were identical to those of the natural waters from which the sheet pile samples came from. The experimental results indicate that underwater corrosion rates in nature are only about one tenth to one eighth of the laboratory values. The corrosion rates in nature depend on the media and the corrosion zone. Furthermore, in laboratory test procedures, the initial corrosion is always tested whereas in nature a "protecting" layer of rust is formed, that lowers corrosion. Therefore, comparison of the values of the experiments with those from nature should be defined in accordance to age and zone of hydraulic steel structures. As a consequence, a corrosion coefficient with consideration of the age of structures was formed. The introduction of the coefficients's dependence on the lifetime of the construction allows improved corrosion rate predictions when the chemical composition of the immersion media is detected. Abstract : Corrosion rates in nature and those obtained in the laboratory are different. The investigation of 15 different mild steel samples from different sheet pile structures in nature and in the laboratory resulted in a corrosion coefficient. The model solutions for the experiments match each of the 15 natural data referring to the pH‐value and the electrical conductivity.